Eliminating Social Homelessness: Providing a Home to Grow - Kevin Duquette; Patrick Akos; Rydell Harrison (Middle Grades Review, 2016)
Middle school students who belong to marginalized identity groups often experience alienation and isolation. These feelings are compounded for multi-marginalized students who experience social homelessness–a term Harrison (2015) uses to describe students who appear to be accepted in one or more social categories but, because of his or her competing identities, is unable to fully participate in the life of the social group without hiding a part of his or her identity. In addition to this internalized struggle, emerging research indicates that socially homeless students are at an increased risk for bullying and academic failure. Inspired by the need to build "homes" for students experiencing social homelessness and our professional experiences with student alienation and underachievement, we created a school-wide house system to promote healthy peer relationships for middle grades students. This essay details the motivation and processes behind creating a school-wide house system that promotes a growth mindset and fosters a positive school culture that is inclusive of all students.
Keywords: social homelessness; growth mindset; advisory council